‘Bridge’ to ‘Fence’ A Maritime History of the Straits of Malacca - Ooi Keat Gin (Diponegoro University, 2022)
Oceans, seas, straits and other bodies of water may pose as dividers between lands, but at the same time, function as bridges interconnecting diverse territories. The latter ascribed a positive attribute in characterizing oceans, seas, straits as linkages between islands, and islands with continents. This study emphasizes the history of the Straits of Malacca and its role to the dynamic of world interconnecting networks. The Straits of Malacca (hereinafter the Straits) in the midst of Southeast Asia is a medium of interaction that enjoins the Malay Peninsula (present day West/Peninsular Malaysia) to other parts of the region spanning across to distant Java and Borneo. The Straits, from time immemorial, has functioned as a natural ‘bridge’ of the Malay World, referring to the Malay Archipelago or Nusantara, that largely comprised the greater expanse of insular Southeast Asia. This ‘bridge’ was even more significant in the period prior to the nineteenth century, being apparent as early as the mid-seventh century CE